Region-specific Constraints to Doing Business: Evidence from Russia - Asel Isakova; Alexander Plekhanov (Aussenwirtschaft, 2011)
This paper looks at variation across Russian regions in terms of perceived constraints to doing business using the Business Environment and Enterprise Performance Survey of Russian firms. The analysis identifies a number of region-specific business environment components that businesses perceive as significantly more binding constraints to their operations compared with other regions. For several business environment components, however, including corruption and access to finance, inter-regional differences in their perception as constraints are insignificant.This is consistent with the view that large observed differences in actual financial deepening across Russian regions are primarily demand-driven.
Keywords: O17; O43; R58; 330; Business climate; Institutions; Regional policies; Russia